Behavior Of Rural Women Of Special Region Of Yogyakarta (Diy) In An Effort To Prevent Menopausal Complaints And Weight Gain - Dame Evalina Simangunsong; Rosa Delima Ekwantini; Marlisa Marlisa (Politeknik Kesehatan Kemenkes Mamuju, 2023)
Periodically, a woman's reproductive function will experience significant changes with age. Various complaints are experienced at this time ranging from mild to severe somatic complaints and even an increase in Body Mass Index (BMI). This study aims to identify increases in weight, blood pressure, menopausal complaints and complaint control behaviors experienced during menopause in 70 menopausal women in DIY in 2020. It was found that as many as 65.7% of women had menopause in the age group of 53-55 years, the highest level of education (72.8%) in the low category (elementary, junior high), working mothers (84.3%), the age of marriage was ≤ 20 years (81.4%) and had children > 2 people (72.9%). It was found that as many as 28 people (40%) had BMI in the fat and obesity categories, 42 people (60%) had blood pressure in the prehypertensive to hypertensive categories, had the heaviest menopausal complaints in complaints of discomfort in the joints and muscles (pain in the joints, rheumatic complaints) and behavior towards efforts to control menopausal complaints in the form of frequency and regular eating patterns until physical activity was considered still low. Ongoing health education efforts are needed for women in rural areas related to the impact of menopause and efforts to prevent complaints and weight gain experienced after menopause.